Cardiotoxicity and cardiovascular biomarkers in patients with breast cancer: data from the GeparOcto‐GBG 84 trial - Rüger, Alexandra Maria; Schneeweiss, Andreas; Seiler, Sabine; Tesch, Hans; van Mackelenbergh, Marion; Marmé, Frederik; Lübbe, Kristina; Sinn, Bruno; Karn, Thomas; Stickeler, Elmar; Müller, Volkmar; Schem, Christian; et al. (Journal of the American Heart Association, 2020)
BackgroundPatients with breast cancer can be affected by cardiotoxic reactions through cancer therapies. Cardiac biomarkers, like NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide) and high‐sensitivity cardiac troponin T, might have predictive value.Methods and ResultsEchocardiography, ECG, hemodynamic parameters, NT‐proBNP and high‐sensitivity cardiac troponin T were assessed in 853 patients with early‐stage breast cancer randomized in the German Breast Group GeparOcto‐GBG 84 phase III trial. Patients received neo‐adjuvant dose‐dense, dose‐intensified epirubicin, paclitaxel, and cyclophosphamide (iddEPC group, n=424) or paclitaxel, non‐pegylated doxorubicin, and in triple negative breast cancer, (paclitaxel, non‐pegylated doxorubicin, carboplatin group, n=429) treatment for 18 weeks. Patients positive for human epidermal growth receptor 2 (n=354, 41.5%) received monoclonal antibodies on top of allocated therapy; 119 (12.9%) of all patients showed a cardiotoxic reaction during therapy (15 [1.8%] using a more strict definition). Presence of cardiotoxic reactions was irrespective of treatment allocation (P=0.31). Small but significant increases in NT‐proBNP developed early in patients with a cardiotoxic reaction as compared with those without in whom NT‐proBNP rose only towards the end of therapy (P=0.04). High‐sensitivity cardiac troponin T rose early in both groups. Logistic regression showed that NT‐proBNP (odds ratio [OR], 1.03; 95% CI, 1.008-1.055; P=0.01) and hemoglobin (OR, 1.31; 95% CI, 1.05-1.63; P=0.02) measured at 6 weeks after treatment initiation were significantly associated with cardiotoxic reactions.ConclusionsNT‐proBNP and hemoglobin are significantly associated with cardiotoxic reactions in patients with early‐stage breast cancer undergoing dose‐dense and dose‐intensified chemotherapy, but high‐sensitivity cardiac troponin T is not.RegistrationURL: http://www.clinicaltrials.gov; Unique identifier: NCT02125344.
Gesehen am 03.02.2021